Pemurnian Emas dari Bijih Emas Berkadar Rendah Menggunakan Karbon Aktif dari Arang Tempurung Kelapa - Mulyasuryani, Ani; Ismuyanto, Bambang; Purwonugroho, Danar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The activated carbon from the coconut shell can be used as an adsorbent for the recovery of gold. The optimum condition for gold recoverywas obtained at pH 3 (for adsorption) and pH 5 (for desorption) with 1 M thyocyanate solution and a 5 cm length of column (the mass ofactivated carbon is 20 grams). In this condition, the average gold recovery is 90.00%, silver 7.28% and copper 4.93%, that were used severalgold ore samples. The average purity degree of gold is 49.67%, depend on the concentration of gold, silver and copper in the gold oresample.